The effect of target breeding and presynch-ovsynch synchronization methods on conception rate in postpartum first insemination in holstein breed cows - Kübra Karakaş Alkan; Hasan Alkan (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine the effect of target breeding and presynch-ovsynch synchronization protocols on the conception rate in the first insemination in Holstein breed cows. Materials and Methods: Study material was consisted of 160 healthy Holstein cows within 30-35 days postpartum and 2.5-6 year of age. The cows were first examined by rectally and ultrasonographically and animals without any problems in the genital system were included in the study. The animals were divided into 3 groups. Group 1 (Target breeding, n = 60) cows were injected with PGF2? three times at 14 days intervals. After the third injection of PGF2?, animals showing estrus up to 72 hours were inseminated. Animals that did not show estrus were inseminated in fixed time at 80th hour. In the second group (Presynch-Ovsynch, n = 50) cows were injected with PGF2? twice 14 days apart and Ovsynch protocol was started 12 days following the second PGF2? injection. Cows in the third group (Control, n = 50) did not receive any treatment. Postpartum first insemination day and conception rates were recorded. Pregnancy examinations of cows were performed by ultrasonography on the 30th day following insemination. Results: Pregnancy rates in target breeding, presynch-ovsynch and control groups were as 36.66% (22/60), 32.0% (16/50) and 24.0% (12/60), respectively (p>0.05). In the target breeding group, estrus was observed in 38 (63.33%; 38/60) cows within 72 hours following the last injection of PGF2?. Pregnancy rates were 42.10% (16/38) and 27.27% (6/22) in inseminated cows by showing estrus and fixed-time inseminated cows without showing estrus, respectively. Conclusion: Although the conception rates after the first insemination did not increase statistically in the target breeding and presynch-ovsynch groups, higher conception rates were obtained in these groups compared to the control group. In conclusion, it is thought that these synchronization protocols may have a positive effect in the first service period however; further studies with more animals are needed.